Advances in artificial intelligence-based microbiome for PMI estimation - Wang, Ziwei; Zhang, Fuyuan; Wang, Linlin; Yuan, Huiya; Guan, Dawei; Zhao, Rui (Frontiers in Microbiology, 2022)
Postmortem interval (PMI) estimation has always been a major challenge in forensic science. Conventional methods for predicting PMI are based on postmortem phenomena, metabolite or biochemical changes, and insect succession. Because postmortem microbial succession follows a certain temporal regularity, the microbiome has been shown to be a potentially effective tool for PMI estimation in the last decade. Recently, Artificial intelligence (AI) technologies shed new lights on forensic medicine through analyzing big data, establishing prediction models, assisting in decision making, etc. With the application of next-generation sequencing (NGS) and AI techniques, it is possible for forensic practitioners to improve the dataset of microbial communities and obtain detailed information on the inventory of specific ecosystems, quantifications of community diversity, descriptions of their ecological function, and even their application in legal medicine. This review describes the postmortem succession of the microbiome in cadavers and their surroundings, summarizes the application, advantages, problems, and future strategies of AI- based microbiome analysis for PMI estimation of AI.